2018
DOI: 10.1002/jocb.234
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Creativity Training on Creative Performance and Creative Self‐Efficacy: Evidence from a Longitudinal Study

Abstract: In organizations and educational institutions, creativity trainings are the preferred approach to enhancing individual creative abilities. However, three issues regarding these trainings still remain largely unsolved. First, the question of how long‐lasting creativity training effects are has not been sufficiently answered so far. Second, the question arises whether all participants benefit from such trainings equally in terms of their creative performance (CP). Third, an increasing number of studies have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 74 publications
4
27
0
2
Order By: Relevance
“…They promote employees' creative ideas and inspiration through exchange and learning from each other during daily life and work, thus improving creativity. This study also verified that creative self‐beliefs are influenced by training and the behaviour of parents and peers (Beghetto & Karwowski, ; Meinel, Wagner, Baccarella, & Voigt, ) and introduced the mechanism of these effects. Individuals' creative self‐beliefs and creative identities are formed in a creative environment constructed by parents and supervisors.…”
Section: Discussionsupporting
confidence: 73%
“…They promote employees' creative ideas and inspiration through exchange and learning from each other during daily life and work, thus improving creativity. This study also verified that creative self‐beliefs are influenced by training and the behaviour of parents and peers (Beghetto & Karwowski, ; Meinel, Wagner, Baccarella, & Voigt, ) and introduced the mechanism of these effects. Individuals' creative self‐beliefs and creative identities are formed in a creative environment constructed by parents and supervisors.…”
Section: Discussionsupporting
confidence: 73%
“…Professional (H1a) and everyday (H1b) creativity should be higher during lockdown than prior to it. Recent research has indicated that creativity training benefits less those individuals who have high baseline creativity ( Meinel et al, 2019 ). Thus, there seems to be a certain learning curve for creativity, and participants with lower creativity may benefit more from the lockdown conditions than those who have a high baseline level of creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Third, as part of creativity training, divergent thinking could enhance general self-efficacy, rather than merely promote creative self-efficacy in the field of creativity ( Mathisen and Bronnick, 2009 ; Byrge and Tang, 2015 ; Meinel et al, 2019 ). In our research, we chose divergent thinking training rather than creativity training as the manipulation; however, we believe creativity training could be effective in promoting self-efficacy and lowering anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the confirmed effect of creative self-efficacy on divergent thinking, some studies examined how creativity training promoted creative self-efficacy ( Mathisen and Bronnick, 2009 ; Byrge and Tang, 2015 ). For instance, Meinel et al (2019) conducted creativity training lasting several months and found enhancement of creative self-efficacy. Similarly, Byrge and Tang (2015) implemented a complex creativity training program that consists of five sections, and the results showed increase in both creative self-efficacy and creativity ability.…”
Section: Introductionmentioning
confidence: 99%